Toxic effect of the herbicide Cold Topic 80EC on the gills of Gambusia holbrooki Girard, 1859 (Journal of the College of Basic Education, 2022)
Aquatic toxicity risks of herbicides to non-target organisms specially fishes are pivotal. The use of pesticides for an effective control of unwanted vegetation has become crucial in the last decades in the agriculture system since it is estimated that thay are cause a yield reductions of almost 20% of crops worldwide. In the last decades, the use of herbicides in agriculture for herbs control has become crucial. As known, , herbicides and other chemicals can enter to water bodies through rain water, food, irrigation water or rivers in many cases and may be hazardous for living systems. These chemicals influence histopathological alteration in all vital organs,Freshwater fish (Gambusia holbrooki Girard, 1859),were exposed to a sublethal concentrations(2,34 and 5,58 mg/l )of commercial grade herbicide gold topik (80% Emulsified Concentrate) for 15 and 30 days.The histological sections of gills examined under light microscope showed severe structural alterations like mucus cells hyperplasia,Degeneration of the secondary lamella ,necrosis in pillar cells and enlargement of mucus cells.